THE INFLUENCE OF MACRO ECONOMY ON THE FIRM VALUE: INVESTMENT DECISION AS THE MEDIATING VARIABLE - Lestari, Oktavia R.; Sukoharsono, Eko Ganis; Rahardjo, Kusdi; Hsu, Wen-Hsi Lydia (FIA UB, 2014)
The purpose of this paper is to investigate the influence of macro economy on the firm value with investment decision as the mediating variable. This study is tested in Indonesia Stock Exchange as one of emerging market. The sample in this study is the manufacture companies listed on the Indonesia Stock Exchange in 4-years period from 2009-2012. Structural equation modelling with Partial Least Square (PLS) is used in this study. This paper found a significantly negative influence between macroeconomy and investment decision, and a significantly positive influence between investment decision and firm value. This paper also analyze whether investment decision can mediate the relationship between macroeconomy and firm value. The result showed that macroeconomy has a significant negative direct effect on the firm value. When investment decision appears on the relationship of macroeconomy and firm value, macroeconomy does not have significant negative influence on the firm value anymore. This result showed that when macroeconomy condition goes down, a firm can retain its value because that firm still earn the profit from its investment and that firm makes the best investment decision. Â Keywords: Macroeconomy, Investment Decision, Firm Value, Partial Least Square